Globally Correlated Ground Magnetic Disturbances During Substorms. Issue 4 (8th April 2021) - Ohtani, Shinichi; Imajo, Shun; Nakamizo, Aoi; Gjerloev, Jesper W.
Abstract: We observationally address substorm‐related ground magnetic disturbances in terms of the substorm current wedge (SCW) system. The study consists of three data analyses, which approach different aspects of this subject. First, by comparing nightside magnetic disturbances below and above the ionosphere, we confirm that substorm‐related midlatitude magnetic disturbances around the edges of the SCW can be attributed to a remote current system (i.e., SCW) rather than to a local ionospheric current. Second, we statistically examine the magnetic local time (MLT) distributions of the correlation between midlatitude magnetic variations and the nightside westward auroral electrojet (AEJ). We confirm that nightside magnetic disturbances are consistent with the SCW, and find that correlated magnetic variations extend to the midday sector. Finally, we introduce midlatitude and high‐latitude geomagnetic indices for each MLT quadrant, and find that their variations are often correlated with the nightside AEJ intensity. From the magnitude of the correlated variations it is inferred that midday magnetic disturbances at both midlatitudes and high latitudes are remote effects of the SCW. In the dawn‐sector and dusk‐sector auroral zone, in contrast, correlated magnetic disturbances can be attributed mostly to the global enhancement of AEJs, which suggests that the global region‐1 system also changes in correlation with the nightside westward AEJ during substorms. These results consistently indicate that ground magnetic disturbances are correlated globally with the substorm westward AEJ. In contrast, the geomagnetic effect of midlatitude ionospheric currents must be relatively small not only on the night side but also on the day side. Key Points: Remote magnetic effects of the substorm current wedge extend to midday midlatitudes masking the effect of local ionospheric currents During substorms, midday midlatitude magnetic disturbances are correlated with the nightside, rather than dayside, auroral electrojets During substorms, the dawnside westward and duskside eastward auroral electrojets often change in correlation with the nightside electrojet